In-situ fabrication of multifunctional N-doped hybrid carbon nanotube@carbon fiber by recycling gaseous effluents of carbon fiber production. (30th June 2022) - Liu, Chao; Miao, Lili; Zhao, Ruixi; Yang, Fangli; Unnikrishnan, Vishnu; Rana, Rohit; Deng, Nanping; Ghandehari Ferdowsi, Mahmoud Reza; Chao, Qi; Kang, Weimin; Razal, Joselito M.; Miao, Liyan; et al.
Abstract: Gaseous effluents from carbon fiber (CF) production process contain a mixture of compounds, in which hydrogen cyanide (HCN), an extremely toxic gas accounts for the largest proportion, together with ammonia, oxocarbon and hydrocarbons. In this work, the successful recovery of gas wastes via the CF loading with iron nanoparticles deposition as catalysts was proved by studying the various stages in the continuous carbonization process of precursor fibers. Significantly, up to 61.2% of HCN during the entire carbonization process (300–1000 °C) is converted into nitrogen-doped carbon nanotubes (CNTs) in-situ on CF surface (CNT@CF). In addition, carbon dioxide and ammonia are also notably reduced at certain temperature ranges. The effect of the gaseous effluents, iron nanoparticles and process parameters on the development of CNT surface morphology as well as structural quality was comprehensively studied. Moreover, the optimized hybrid structure of CNTs created onto CF surface contributes to noteworthy interfacial property improvement (95%) of structural composite and improved reversible capacity (96 F/g at 1 A/g) and exceptional cycling performance of supercapacitors. This work reveals a facile in-situ technique for efficiently recycling the toxic gas emissions of CF production as well as synthesizing multifunctional nanomaterials at a large scale. Graphical abstract: Image 1